Respuesta :

Answer:

z = 11

Step-by-step explanation:

Simplifying

17 + 3(z + -2) + -11z = -7(z + 2) + 14

Reorder the terms:

17 + 3(-2 + z) + -11z = -7(z + 2) + 14

17 + (-2 * 3 + z * 3) + -11z = -7(z + 2) + 14

17 + (-6 + 3z) + -11z = -7(z + 2) + 14

Combine like terms: 17 + -6 = 11

11 + 3z + -11z = -7(z + 2) + 14

Combine like terms: 3z + -11z = -8z

11 + -8z = -7(z + 2) + 14

Reorder the terms:

11 + -8z = -7(2 + z) + 14

11 + -8z = (2 * -7 + z * -7) + 14

11 + -8z = (-14 + -7z) + 14

Reorder the terms:

11 + -8z = -14 + 14 + -7z

Combine like terms: -14 + 14 = 0

11 + -8z = 0 + -7z

11 + -8z = -7z

Solving

11 + -8z = -7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '7z' to each side of the equation.

11 + -8z + 7z = -7z + 7z

Combine like terms: -8z + 7z = -1z

11 + -1z = -7z + 7z

Combine like terms: -7z + 7z = 0

11 + -1z = 0

Add '-11' to each side of the equation.

11 + -11 + -1z = 0 + -11

Combine like terms: 11 + -11 = 0

0 + -1z = 0 + -11

-1z = 0 + -11

Combine like terms: 0 + -11 = -11

-1z = -11

Divide each side by '-1'.

z = 11

Simplifying

z = 11

Z equals 11 you’re welcome mark me brainliest
ACCESS MORE